Congenital adrenal hyperplasia - experience from a tertiary centre in South India - Belinda, George (Medknow Publications & Media Pvt Ltd, 2012)
Congenital adrenal hyperplasia is a group of autosomal recessive disorders caused by enzyme deficiency which leads to defects in biosynthesis of steroid precursors. Most common is 21 hydroxylase deficiency. Clinical spectrum varies from non-classical CAH to classic CAH, and it may be simple virilising form or salt-wastinfg type. 29 patients were included in our study from January 2012 to October 2012. 76% were females. Male babies typically presented with adrenal crisis between 3(rd) to 6(th) week of life. Around 20% of females were identified and appropriately treated only after late adolescence. Short stature was seen in 1/3(rd) of patients. 1/3(rd) of patients had suppressed 17 OHP levels suggestive of over-replacement therapy which may contribute to final reduction in adult height.